Front Cover, Volume 43, Issue 11. Issue 11 (11th October 2022) - Scott, Stuart A.; Wang, Kai; Spinner, Nancy B.
Abstract : Front Cover : Image design credit: Shiva Ganesan, Laura K. Conlin, and Ramakrishnan Rajagopalan. The cover image is based on the Editorial Introduction Human Mutation special issue on innovations in genomic diagnostics by Stuart A. Scott et al., https://doi.org/10.1002/humu.24474 .